2016
DOI: 10.4314/ahs.v16i3.24
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of alcohol use and khat chewing among Hawassa University students, Ethiopia: A cross sectional study

Abstract: Background: Students' alcohol and khat use have been associated with various health related problems. However, its magnitude and associated factors among Ethiopian students are not yet well documented. Objective: The study aimed to assess the prevalence of alcohol use, khat chewing and its associated factors among Hawassa University students. Methods: A cross-sectional study was conducted from June to July 2011. Multistage stratified sampling technique was employed to select 590 students. Self administered que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(68 citation statements)
references
References 27 publications
6
60
2
Order By: Relevance
“…The other predictive factor which revealed in this study were instructors with a friend history of substance use had a nine times higher risk of substance use as compared to those instructors with no friends history of substance use (AOR = 9.047 [4.645-17.620] [95% CI]). The current study was similar to the study done in Hawassa University students on alcohol and khat use; students who had a friend who uses the substance had 4.6 times higher odds of substance use than those students who had no friends who used substances [33]. Also, the finding of the current study was in line with another study revealed that students who had friends who used substances had 2.14 times higher risk of using substances than those students who had no friends who had used substances, even though the study population was different [31].…”
Section: Discussionsupporting
confidence: 83%
“…The other predictive factor which revealed in this study were instructors with a friend history of substance use had a nine times higher risk of substance use as compared to those instructors with no friends history of substance use (AOR = 9.047 [4.645-17.620] [95% CI]). The current study was similar to the study done in Hawassa University students on alcohol and khat use; students who had a friend who uses the substance had 4.6 times higher odds of substance use than those students who had no friends who used substances [33]. Also, the finding of the current study was in line with another study revealed that students who had friends who used substances had 2.14 times higher risk of using substances than those students who had no friends who had used substances, even though the study population was different [31].…”
Section: Discussionsupporting
confidence: 83%
“…Besides, in some of the reported studies that linked khat usage and upper GIT premalignant conditions or cancer (Soufi et al, 1991;Macigo et al, 1995;Ahmed et al, 2010), it was unclear that whether the authors excluded factors like genetics, smoking behaviour and alcohol drinking as other possible reasons which could cause the mentioned conditions and cancer. It has been widely reported that khat consumption is associated with smoking behaviour (Alem et al, 1999;Kebede, 2002;Ayana and Mekonen, 2004;Gorsky et al, 2004;Al-Sanosy, 2009;Douglas et al, 2011;Alsanosy et al, 2013;Kassim et al, 2014;Kubas and Wadi, 2015;Nakajima et al, 2016) and alcohol drinking (Douglas et al, 2011;Reda et al, 2012;Kassa et al, 2016). These two factors had been widely recognized as the risk factors for upper GIT cancer (Morse et al, 2007;Ram et al, 2011;Perry et al, 2015) and if these two factors were not carefully considered in the mentioned studies, this could raise a big bias query.…”
Section: Moderate (+++)mentioning
confidence: 99%
“…Also, since the data collections have done inside the teaching classroom, those students with addiction behaviors may remain outside the classroom because of their academic and living lifestyle. This can potentially introduce sampling bias and result in a lower estimate of alcohol drinking (18).…”
Section: Discussionmentioning
confidence: 99%